Development of a web-platform for dynamic monitoring of population health in Geneva: Specchio project. (30th September 2020) - Baysson, H; Joost, S; Attar Cohen, H; Guessous, I; Stringhini, S
Abstract: Background: In order to provide efficient public health decisions making, it is crucial to obtain reliable and recent data on the state of health of the population. For that purpose, a web-platform for the dynamic monitoring of the health status and well-being of the population is being developed in the Geneva canton. Methods: Using a dedicated website, recruitment will be carried out over 5 years so as to enroll up to 20 000 volunteers, resident in Geneva and aged ≥ 18 years, followed-up for at least 10 years. Once connected to the website, participants will fill a general self-administered questionnaire on their socio-demographic and lifestyle characteristics, anthropometry, health status, physical activity and diet. Environmental, behavioral and occupational exposures will also be evaluated via more specific questionnaires. Current addresses of residence will be geocoded and linked to geographical databases to passively gather information on noise, air pollution, green areas, and other exposures. Surveillance of health events will be implemented via yearly self-administered on line questionnaires and potentially via passive linkage to medical databases (medical file) and health registries with the participants' consent. For a subsample of volunteers, biochemical samples and biomarkers will be collected. Results: The pilot study shows that the project is feasible, potentially cost-effective but requires innovative methodologies for ensuring long term follow-up. Different communication strategies used for recruitment and long-term participation need to be implemented ensuring trust from participants, different levels of health literacy and the need of justice. Conclusions: Specchio is a new project aimed at setting up a digital longitudinal health study in Geneva. Challenges concerns the determinants of participation, recruitment and attrition, quality of data and ethics. Long-term funding by the Directorate General of Health Geneva is currently under evaluation. Key messages: This digital longitudinal health study will enable dynamic monitoring of the health status and well-being of Geneva residents and will enable efficient public health decision making. Specchio is a new project funded by the Directorate General of Health Geneva.